2015
DOI: 10.1111/cas.12833
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical activity of the novel B‐cell‐specific Moloney murine leukemia virus integration site 1 inhibitor PTC‐209 in acute myeloid leukemia: Implications for leukemia therapy

Abstract: Curing patients with acute myeloid leukemia (AML) remains a therapeutic challenge. The polycomb complex protein B‐cell‐specific Moloney murine leukemia virus integration site 1 (BMI‐1) is required for the self‐renewal and maintenance of leukemia stem cells. We investigated the prognostic significance of BMI‐1 in AML and the effects of a novel small molecule selective inhibitor of BMI‐1, PTC‐209. BMI‐1 protein expression was determined in 511 newly diagnosed AML patients together with 207 other proteins using r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
32
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 38 publications
(77 reference statements)
6
32
1
Order By: Relevance
“…Considering that BMI inhibitors did not significantly affect the viability of normal lymphocytes, our data indicate that they could be candidates for novel molecular targeting drugs against leukemia. Because BMI1 regulates cell stemness (5,6), BMI inhibitors could be used as drugs targeting leukemia stem cells. However, more research should be conducted to clarify molecular pathways targeted by BMI inhibitors and ensure their safety for normal hematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that BMI inhibitors did not significantly affect the viability of normal lymphocytes, our data indicate that they could be candidates for novel molecular targeting drugs against leukemia. Because BMI1 regulates cell stemness (5,6), BMI inhibitors could be used as drugs targeting leukemia stem cells. However, more research should be conducted to clarify molecular pathways targeted by BMI inhibitors and ensure their safety for normal hematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…B cell-specific Moloney murine leukemia virus integration site 1 (BMI1) is a key regulatory component of PRC1 (4) known to promote cell proliferation by inhibiting expression of various genes such as cyclin-dependent kinase inhibitor 2A (CDKN2A) which encodes CDK inhibitor p16 INK4A and tumour suppressor p14 ARF . BMI1 was shown to be upregulated in several cancers, including acute leukemia (4)(5)(6), and a novel small molecule inhibitor of BMI1, PTC-209, has demonstrated inhibitory activity in human colorectal cancer (7), acute leukemia (6), and myeloma (8).…”
mentioning
confidence: 99%
“…Bmi-1 gene was initially isolated as an oncogene in a retroviral-induced B- and T-cell leukemia, and it plays an essential role in leukemia stem cells 19,20. Bmi-1 deletion can inhibit tumor stem cell self-renewal and prevent leukemic recurrence 21. In addition, overexpression of Bmi-1 was found in many cancers and was used as an important marker for predicting the progression to acute myeloid leukemia,22 consistent with our recent findings in ICC.…”
Section: Discussionmentioning
confidence: 99%
“…19 In mouse models with patient-derived colorectal cancer, PTC-209 potently suppressed tumor growth and eradicated cancer-initiating cells. 21 We reported that PTC-209 induces apoptosis in AML patient-derived CD34 + CD38 low/− stem/progenitor cells.…”
Section: Introductionmentioning
confidence: 99%